Journal of technical education seience (Ho Chi Minh city University of Technology and Education, 2018)
Contents: study and manufacture of the low temperature vacuum drying system in pillot scale; a review paper on radial junction silicon nanowire solar cells; biodegradable polymer layers for production of smart urea fertilizer by coating pan system;...